FOSTERING RELIGIOUS VALUES FOR MEMBERS OF GP. ANSOR RANTING KEBOJONGAN VILLAGE, COMAL PEMALANG DISTRICT - Ma'ruf, Amar; Tazali, Imam; Suryanti, Ery; Zulfa, Puspa Fortuna (Jurnal Konseling Pendidikan Islam, 2024)
The purpose of this research is to analyze the development of religious values of Ansor Youth Movement (GP Ansor) members. One of the religious-based community organizations capable of realizing the nation's progress is the Ansor Youth Movement (GP Ansor). How much and how far religious values can influence and shape a person's character depends on how much religious values are embedded in him. This research includes field research, with a qualitative approach, which is research that produces analytical procedures that do not use statistical analysis. The data obtained were then analyzed using qualitative descriptive analysis techniques. The results of this study show that religious values are fostered by members of GP Ansor Kebojongan Branch by giving good advice, teaching about morals from the book of Taitsirul Kholaq and Akhlakul Banin, as well as teaching the book of Aqidatul Awwam and holding additional activities such as maulidan activities, grave pilgrimage prayers, and others. While the supporting factor is the development of religious values for members of GP. Ansor Ranting Kebojongan, Comal Sub-District, Pemalang Regency is the recitation of the book of Taisul Kholaq, and support from the community, while the inhibiting factors are inadequate infrastructure and the busyness of the members.